Gaussia Luciferase for Bioluminescence Tumor Monitoring in Comparison with Firefly Luciferase - Yusuke Inoue; Fugeng Sheng; Shigeru Kiryu; Makoto Watanabe; Harnprasopwat Ratanakanit; Kiyoko Izawa; Arinobu Tojo; Kuni Ohtomo (Molecular Imaging)
Gaussia luciferase (Gluc) is a secreted reporter, and its expression in living animals can be assessed by in vivo bioluminescence imaging (BLI) or blood assays. We characterized Gluc as an in vivo reporter in comparison with firefly luciferase (Fluc). Mice were inoculated subcutaneously with tumor cells expressing both Fluc and Gluc and underwent Flue BLI, Gluc BLI, blood assays of Glue activity, and caliper measurement. In Gluc BLI, the signal from the tumor peaked immediately and then decreased rapidly. In the longitudinal monitoring, all measures indicated an increase in tumor burden early after cell inoculation. However, the increase reached plateaus in Gluc BLI and Fluc BLI despite a continuous increase in the caliper measurement and Gluc blood assay. Significant correlations were found between the measures, and the correlation between the blood signal and caliper volume was especially high. Gluc allows tumor monitoring in mice and should be applicable to dual-reporter assessment in combination with Fluc. The Gluc blood assay appears to provide a reliable indicator of viable tumor burden, and the combination of a blood assay and in vivo BLI using Glue should be promising for quantifying and localizing the tumors.